PENERAPAN PENDEKATAN LINGKUNGAN UNTUK MENINGKATKAN HASIL BELAJAR KELAS VIII SEMESTER I DI MTSN PESISIR SELATAN KABUPATEN PESISIR SELATAN - Sari, Selvi Kurnia (STKIP PGRI Sumbar, 2014)
The achievement of learning biology cannot achieve the standard of KKM at MTsN Pesisir Selatan it is because less of studentsâ interest and studentsâ motivation to learn, the teacher only use lecture method to explain the material, the teacher does not use appropriate method in learning process. The method makes the student feel bored in teaching and learning process. It also makes the students going out from classroom. The students can not pay attention with the teachersâ explanation. Because of that, the rescarcher find an approach to solve the problems above, it is the environment approach. In this approach, the teacherasks the students to pay attention to the objeck that will learn by them. The purpose of this research is to know the effect of the environment approach toward studentsâ achievement in learning biology at the eighth (VIIIc) in academic year 2012/2013. This researcher is an experiment research with randomzed control group design. The population of this research is the students of VIIIb class as control class, the studentsâ of VIIIc class experiment class. For data analysis, the researcher uses t-test. the researcher found that in experiment class it has 63,46 on overange it is higher that control class. The contol class 43,75.and t hitung is 4,38 and t table 1,68,therefore, t calculate >t table. It can conluded that the environment approach can improve the learning auto come of biology at eighth studenst at MTsN Pesisir Selatan.